Thermal Buoyancy Effects in Rotating Non-Isothermal Flows - C. Y. Soong (International Journal of Rotating Machinery)
The present paper is concerned with the non-isothermal flow mechanisms in rotating systems with emphasis on the rotation-induced thermal buoyancy effects stemming from the coexistence of rotational body forces and the nonuniformity of the fluid temperature field. Non-isothermal flow in rotating ducts of radial and parallel modes and rotating cylindrical configurations, including rotating cylinders and disk systems, are considered. Previous investigations closely related to the rotational buoyancy are surveyed. The mechanisms of the rotation-induced buoyancy are manifested by the author's recent theoretical results and scaling analyses pertaining to the rotation-induced buoyancy in rotating ducts and two-disk systems. Finally, the open issues for future researches in this area are proposed.